Motivaciones turísticas y satisfacción del turista mochilero que visita la ciudad de Iquitos 2021 - Trigozo Cenepo de Flores, Maria Graciela (2022)
The research aimed to determine the relationship between tourist motivations and satisfaction of the backpacker tourist, who visits the city of Iquitos, 2021. The type of study used was quantitative, non-experimental, cross-sectional and correlational design; with a sample of 60 tourists. The instruments used were: a Likert Scale, which allowed to measure the tourist motivations, consisting of 24 items, grouped into five dimensions: Needs for fulfillment, self-esteem and development, relationship, protection and security, and physiological; whose validity was 88.52% and reliability 90.46%; a Questionnaire that allowed to measure the satisfaction of the backpacker tourist, according to their expectation, reasons of pleasure and displeasure, tourist attractions and tourist services; whose validity was 87.23% and reliability 89.43%. The following results were obtained: of the 100% (60) of backpacker tourists, 93.3% (56) presented a high level of motivation and 6.7% (4) average motivation. 80.0% (48) said they were satisfied and 20.0% (12) dissatisfied. By relating both variables under study, it was determined that there is a significant statistical relationship (X2 = 8.103; p = 0.004; gl = 1 < 0.05) between tourist motivations and the satisfaction of the backpacker tourist, when visiting the city of Iquitos. These findings allow to strengthen the area of tourism marketing; at the same time, segment markets of different tourist activities, with preference to this segment of tourists and thus, continue to compete within the national and international market.